PHYTOSANITARY STATE OF THE AGROECOSYSTEM OF WINTER WHEAT DEPENDING ON THE PRECINCENTS OF PERENNIAL LEGUMES - A.P. Tkachuk (Uman National University of Horticulture, 2021)
The article is devoted to solving the problem of increasing the resistance of winter wheat crops to the effects of the most common diseases, weeds and pests during its cultivation after the predecessors of six types of perennial legumes without the use of pesticides. The percentage of damage to the leaf surface of winter wheat with diseases of septoria and powdery mildew is shown. The number of the soil pest of the May beetle larvae was analyzed. The level of weediness of winter wheat crops in the context of predecessors was investigated with the determination of superior weed species after each of them. The level of grain yield of winter wheat, depending on the predecessors, was investigated and correlation-regression relationships between it and the spread of pests, diseases and weeds in their crops were revealed. A close correlation has been proved between the yield of winter wheat grain and the percentage of damaged leaf area by powdery mildew disease. It is shown that the highest level of grain yield of winter wheat is observed after the predecessor of meadow clover. The smallest damage to the leaf surface of winter wheat plants by powdery mildew disease was found after the predecessor of meadow clover. The defeat of the leaf surface of winter wheat by the disease septoria was the least after the predecessor of the sweet clover. During the sowing period of winter wheat, no larvae of the May beetle pest were found in the arable soil layer after the predecessors of alfalfa, sweet clover and eastern goat's rue. The smallest amount of weeds during the spring growth of winter wheat was found after the predecessor of the sweet clover.